AN ERROR ANALYSIS ON SYNTACTICAL ERRORS IN STUDENTS’ ENGLISH WRITING - Adlina, Nuri; Amalia, Desthia (Universitas Gunadarma, 2021)
English has been studied for many years in Indonesia, it is important to recognize some common errors that are produced by the learners in order to help them improving. Therefore, this research aims to investigate the types and sources of syntactical errors that occur on fifth-semester students’ English writing. A qualitative descriptive method is used in this study. The results show there are 25 syntactical errors that consist of 3 errors in phrases and 22 error in clauses. The writers found there are 22 errors in clause. Furthermore, errors in clause the percentage show that misselection with 63%, addition with 23%, omission with 14% and misorder with 0%. Meanwhile, errors in clause, misselection error is the most frequent error occurred. Then, there are two sources of errors namely interlingual and intralingual errors. The writers found 8 data as interlingual errors and 17 data as intralingual errors. The intralingual errors are divided into four categories named overgeneralization (3 data). ignorance of rule restriction (10 data), incomplete application of rule (3 data), and false concept of hypothesis (1 datum).